A função pedagógica da arte na formação de educadores - Margarete Bertollo Boccia; Patricia Bioto-Cavalcanti (EccoS – Revista Científica)
In this text is systematized the experience of teachers formation in service grounded in pedagogical function of art, whose moments of formation started from reflections upon through screens of Tarsila do Amaral and Candido Portinari. First of all, it exposes the theoretical foundations that supported the discussions. Furthermore, it permeates the discussion of values and attitudes present in the work of professionals who worked there, in addition the reflections about the school routine to allow the establishment of agreements on ways and practices. Finally, it presents a report about experiences during the meetings, as well as an analysis of the movements that it has raised.